Examining the nomological validity of work engagement drivers: a study on the relevance of covid-19 key factors in the post-pandemic era - Fitriani, Arbania; Situmorang, Dominikus David Biondi; Putri, Yola Eka; Yani, Ani (COUNS-EDU: The International Journal of Counseling and Education, 2024)
Work engagement has become a critical factor in maintaining organizational performance, particularly in the context of unprecedented global challenges such as the COVID-19 pandemic. This study investigates the key drivers of work engagement during the COVID-19 pandemic and their relevance in the post-pandemic era. Using a cross-sectional design, a structural model was developed based on the Job Demands-Resources (JD-R) model, incorporating job satisfaction as a moderating variable between organizational-personal factors and work engagement. Data were collected from 1,484 public sector employees in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that organizational-personal factors significantly influence job satisfaction and work engagement. Job satisfaction also moderates the relationship between these factors and work engagement, enhancing its impact. The findings highlight the importance of prioritizing health support, skill development, and work-life balance to boost employee motivation and engagement. This research contributes to understanding the evolving dynamics of work engagement amidst global crises and provides actionable insights for human resource management practices. The study underscores the need for adaptive strategies to maintain employee well-being and productivity in changing work environments.